Impact of Technology Integration on Math Achievement in Middle School Classrooms in India - Patel, Aarar (American Journal of Education and Practice, 2024)
Purpose: The aim of the study was to assess the impact of technology integration on math achievement in middle school classrooms in India. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study revealed that the incorporation of technology, such as interactive software and educational applications, positively influences students' engagement and motivation in learning mathematics. This increased engagement leads to enhanced conceptual understanding and problem-solving skills among students. Additionally, technology integration facilitates personalized learning experiences, allowing students to progress at their own pace and receive immediate feedback, which contributes to improved academic performance. Moreover, the study suggests that teachers play a crucial role in mediating the effectiveness of technology integration by effectively integrating it into their instructional practices and providing necessary support to students. Implications to Theory, Practice and Policy: Cognitive load theory, constructivist learning theory and technology acceptance model may be used to anchor future studies on assessing the impact of technology integration on math achievement in middle school classrooms in India. Educators should be encouraged to adopt evidence-based practices that leverage educational technology to enhance math instruction in middle school classrooms. Policymakers play a pivotal role in shaping the educational landscape and allocating resources to support technology integration initiatives in middle school mathematics education.